GOMS-based User Experience for Cultural Tourism Application in Indonesia - Kurniawan, Muhammad David; Haryanto, Hanny (Advance Sustainable Science, Engineering and Technology, 2024)
Indonesia's diverse cultural heritage presents an opportunity for tourism, yet traditional approaches and insufficient technology utilization hinder its full potential. We propose the development of a Cultural Tourism Application, specifically targeting the rich cultural attractions of Yogyakarta, Indonesia. The research develop the GOMS (Goals, Operators, Methods, and Selection Rules) model to design user-friendly interfaces for discovering cultural attractions, providing detailed information, searching, and exploring historical timelines and helped us understand the steps and knowledge required for users to achieve their goals within the app This model allows for a systematic understanding of user interactions and cognitive processes within the context of the Cultural Tourism Application. A User Acceptance Testing (UAT) survey reveals a high level of acceptance 91.2% for the Cultural Tourism Application, signifying its effectiveness in enhancing learnability, efficiency, memorability, safety, and overall user satisfaction.